Proteomic signatures reveal a dualistic and clinically relevant classification of anal canal carcinoma - Herfs, Michael; Suarez-Carmona, Meggy (The journal of pathology, 2016)
Aetiologically linked to HPV infection, malignancies of the anal canal have substantially increased in incidence over the last 20 years. Although most anal squamous cell carcinomas (SCCs) respond well to chemoradiotherapy, about 30% of patients experience a poor outcome, for undetermined reasons. Despite cumulative efforts for discovering independent predictors of overall survival, both nodal status and tumour size are still the only reliable factors predicting patient outcome. Recent efforts have revealed that the biology of HPV-related lesions in the cervix is strongly linked to the originally infected cell population. To address the hypothesis that topography also influences both gene expression profile and behaviour of anal (pre)neoplastic lesions, we correlated both proteomic signatures and clinicopathological features of tumours arising from two distinct portions of the anal canal: the lower part (squamous zone) and the more proximal anal transitional zone. Although microdissected cancer cells appeared indistinguishable by morphology (squamous phenotype), unsupervised clustering analysis of the whole proteome significantly highlighted the heterogeneity that exists within anal canal tumours. More importantly, two region-specific subtypes of SCC were revealed. The expression profile (sensitivity/specificity) of several selected biomarkers (keratin filaments) further confirmed the subclassification of anal (pre)cancers based on their cellular origin. Less commonly detected compared to their counterparts located in the squamous mucosa, SCCs originating in the transitional zone more frequently displayed a poor or basaloid differentiation, and were significantly correlated with reduced disease-free and overall survivals. Taken together, we present direct evidence that anal canal SCC comprises two distinct entities with different cells of origin, proteomic signatures, and survival rates. This study forms the basis for a dualistic classification of anal carcinoma, with implications for management, outcome expectations, and possibly therapy.